Comparison of Hoteling Cost of Global Surgery with Real Cost in Isfahan Public Hospitals, 2012 - AmirHosein Fattahpour; Reza Ebrahimi Dourcheh; Mohsen Rahimi; Noora Rafiee (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Paying for the global surgery is one of the prospective payment methods in which service providers receive their service costs according to a preset table. In this method, payment is based on patients’ treatment not in terms of any remedial action. Therefore, it reduces the motivation of rendering unreasonable service. However, its weak point is making simple diseases complex as well as reducing consumption of resources for patients and etc. Since surgeries are considered as costly items in Iran’s insurance system, the present study targeted at investigating the hoteling cost of global surgery in Isfahan public hospitals. Methods: This descriptive and Applied research has investigated the difference between real hoteling cost of 60 global surgeries and the amount of paid hoteling in global plan in Isfahan public hospitals in 2012. The real hoteling cost of the global surgery (real rate of patients’ hospitalization) was collected through Hospital Information System (HIS).The required information about the global costs was also  obtained from the annual Insurance Council directive on how to calculate the global surgery. Excell software was then used for data analysis. Results: The average of real hospitalization hoteling and paid hoteling costs by the health insurance to the hospital based on the global plan were respectively 1.77 and 2.81 in which the real difference between hospitalization and the calculated amount in global plan is 1.04 day. Conclusion: There was a difference between global cost paid by insurance companies to the hospital and the real cost of surgery in all investigated surgeries so that from 60 cases of global surgery in 53 real hoteling, patient hospitalization was less than the amount paid in global plan of hospitals. Real hoteling was more in just two cases.